Modelling corporate tax reforms in the EU: New simulations with the CORTAX model - Maria Teresa Alvarez-Martinez; Salvador Barrios; Diego d'Andria; Maria Gesualdo; Dimitrios Pontikakis; Jonathan Pycroft (European Commission, Joint Research Centre (JRC), 2016)
This study investigates the economic impact of a recent proposal for a common corporate tax base (CCTB), European Commission (2016a), and a common consolidated corporate tax base with formula apportionment (CCCTB) within the EU, European Commission (2016b). On top of the common base, it considers proposals to reduce the debt bias in corporate taxation. To do so, we employ an applied general equilibrium model (CORTAX) covering all EU Member States, featuring different firm types and modelling many key features of corporate tax regimes, including multinational profit shifting, investment decisions, loss compensation and the debt-equity choice of firms. First, the economic impact of C(C)CTB is assessed, restricting the scope of the reforms to multinationals only. Macroeconomic results show that the common tax base simulations directly affect the cost of capital, which on average falls across the EU, boosting investment, and therefore driving the increase in GDP. Second, C(C)CTB is simulated together with proposals to reduce or eliminate the debt bias in corporate taxation, principally: the comprehensive business income tax (CBIT), the allowance for corporate equity (ACE) and the allowance for corporate capital (ACC). From a financing prospective, all proposals incentivise firms to rely less on debt-financing. From a macroeconomic perspective, the simulations which narrow the tax base by introducing addition deductions, i.e. ACE and ACC, raise GDP, despite the fact that the (ex-ante) CIT revenue is maintained by adjusting the CIT rate. The opposite is the case for the CBIT, which causes a fall in GDP. Third, a group of sensitivity simulations are presented to check for robustness. Among the insights from the sensitivity simulations, one notes that the inclusion of domestic firms in the CCCTB proposal somewhat increases the positive impact on GDP. A broader harmonised tax base results in lower welfare and GDP outcomes than a narrower harmonised tax base, because it more directly impacts the marginal investment decision. Reducing profit shifting slightly lowers investment, though on balance does not negatively impact welfare. The model results are robust to varying the capital-labour substitutability. In summary, the results of this economic modelling evaluation suggest that a fairer and more efficient tax system can be introduced whilst maintaining, and perhaps improving, GDP and welfare in the EU.
Keywords: 330; Computable General Equilibrium model; CORTAX; CCTB; CCCTB; Profit-shifting